Fragments of the Sublime - Arman; Camp, J.R. (New York : J. Camp Associates, Ltd., 1980)
Dogon ; Anyang ; Bamileke ; Bakongo ; Plateau Bouchi ; Segou ; Mambila ; etc.
Fragments of the Sublime, J. Camp Associates, Ltd., New York, March 18 - April 5, 1980
boek
Keywords: Arman; Afrika